European Future of Bulgarian Economy (Is in the Mind and Hands of a Bulgarian) (UNWE Yearbook, 2005)
The paper interprets some issues of the European future of the Bulgarian economy outlining the prerequisites necessary to ensure the most efficient and favorable manner of the country’s accession to the European Union (EU) and its integration in it. It is stressed that the European future of the Bulgarian economy is in the heart and mind of Bulgarians, in other words, this future is what can be imagined by a Bulgarian to be subsequently created and put into practice. The author emphasizes that in order to become an equal and worthy participant in a dialogue with the EU regarding its future presence in a United Europe, the country needs its own well-founded vision of its EU future.The Bulgarian membership in the EU and a European future of the Bulgarian economy are interpreted in their different aspects. It has been argued that the country’s membership in the EU represents a new opportunity of crucial importance for the development of Bulgarian economy. At the same time it may be regarded as a significant constraint of this development. Consequently, the study goes on to explore the thesis that the European future of the Bulgarian economy is a major challenge for the mind and hands of a Bulgarian. Moreover, the future of the Bulgarian economy in the United Europe presents an ordeal, a critical responsibility for the mind and the heart of a Bulgarian. It is furthermore argued that the process of accession and integration of the Bulgarian economy in the EU is a major initiative of extreme complexity and responsibility requiring a mobilization of efforts, energy and talent of the entire nation. Hence one the principal imperatives for the success of this initiative is identifying the responsibilities and rights of every entity with regard to the implementation of the accession strategy. The paper addresses the issues of “lawful” skepticism of Bulgarians in respect of every new policy, including that of accession and integration.The author argues that in the long run, the EU membership should be viewed as multi-faceted and versatile, a step of critical importance for Bulgarians. Consequently, the more this matter has been explored and clarified, the more successful practical measures adopted for its implementation are likely to be. It is argued that the accession and integration of Bulgarian economy in the EU is an objective process which however may be occur in different ways – as a success or failure, in an acceptable or an unacceptable way, Undoubtedly the accession and integration of the Bulgarian economy in the EU is in the interests of the country, but this process is in the interest of Bulgaria as an objective possibility which may be benefited from or wasted.Subsequently the study interprets the idea that the accession of Bulgarian economy to the EU represents an objective process in its inherent character and is part of the process of integration and globalization world-wide. Thus Bulgarian membership in the EU does not signify the country’s isolation from the rest of the world. In other words, Bulgaria’s relations with the EU, on the one hand, and its relations with the rest of the world including Russia, on the other hand do not constitute an “either or”, but rather a “both.. and” relationship.The next section of the paper deals with the relationship between the processes of accession and integration, on the one hand, and a transition to an economy of knowledge, on the other hand. It is argued that the above should go hand in hand, as a single process. The requirements of the EU to Bulgaria as a prospective member state have also been given pride of place. It is suggested that the success of a strategy and policy of accession and integration of Bulgaria within the EU will depend on the extent it meets the objective logic of development and the new realities of the XXI century as well as the requirements imposed by the EU on Bulgaria as a prospective EU member. The paper examines and interprets the criteria for accession and integration in the European Community. The emphasis is laid on the fact that successful implementation of the accession and integration process is in direct relation to the degree the country has been meeting the accession and integration criteria. In this context the accession and integration criteria have been interpreted as an imperative of behavior on micro-, regional- and macro level. Special attention has been directed to the issue of the lessons of the evolution of the EU regional policy. It is argued that it is due to the understanding of the EU regional policy and its evolution that both the requirements imposed by this policy for the regional development of Bulgaria, and the openings for the country’s development may be inferred.At the same time the paper attempts to outline the tendencies for a future change in the regional policy of the EU as a guideline for the integration process management system. This section of the paper lays a special emphasis on the “natural conflict” between the EU member countries and the EU candidates regarding the use of the resources from the structural funds of the Community. In order to develop a high quality system for Bulgaria’s accession and integration in the Union it is necessary to identify and interpret the key problems relating to the economic development of Bulgaria. It is argued that on the one hand these problems pose certain important requirements for the future development, and on the other, they serve as constraints for the development and the process of integration. Subsequently the paper attempts to define competitive advantages of the economy of Bulgaria interpreting their role for the processes of accession and integration of the country. In fact, the author argues that in order to develop a high quality accession and integration strategy it is necessary to identify the advantages of the national and regional economies compared to all other economies.At a subsequent stage, based on the arguments and ideas interpreted and advocated in the preceding sections of the paper, the author goes on to discuss the type of strategy required by the process of the country’s accession and integration to the EU. There is no denying that Bulgaria indeed needs a unique high quality of accession and integration strategy. This is why the development of an integration strategy of the country within the EU is of critical significance for Bulgaria as a key research priority. To contribute to this research the author discusses the role of foreign assistance in the development and implementation of an integration strategy, typical of Bulgaria. The paper also examines the conditions for developing an integration strategy of the country with a view of the changes in the environment for these processes. These changes should be regarded as irreversible – a transition to “an environment without laws.”Finally, the paper argues that it is necessary to have a discussion on the development of an accession and integration strategy. The author emphasizes the necessity to comment on the role played by science in the development of “an architectural project” for the accession and integration of the Bulgarian economy in the EU.